Mapping atmospheric aerosols with a citizen science network of smartphone spectropolarimeters. Issue 20 (27th October 2014) - Snik, Frans; Rietjens, Jeroen H. H.; Apituley, Arnoud; Volten, Hester; Mijling, Bas; Di Noia, Antonio; Heikamp, Stephanie; Heinsbroek, Ritse C.; Hasekamp, Otto P.; Smit, J. Martijn; Vonk, Jan; Stam, Daphne M.; et al.
Abstract To assess the impact of atmospheric aerosols on health, climate, and air traffic, aerosol properties must be measured with fine spatial and temporal sampling. This can be achieved by actively involving citizens and the technology they own to form an atmospheric measurement network. We establish this new measurement strategy by developing and deploying iSPEX, a low‐cost, mass‐producible optical add‐on for smartphones with a corresponding app. The aerosol optical thickness (AOT) maps derived from iSPEX spectropolarimetric measurements of the daytime cloud‐free sky by thousands of citizen scientists throughout the Netherlands are in good agreement with the spatial AOT structure derived from satellite imagery and temporal AOT variations derived from ground‐based precision photometry. These maps show structures at scales of kilometers that are typical for urban air pollution, indicating the potential of iSPEX to provide information about aerosol properties at locations and at times that are not covered by current monitoring efforts.